Modafinil Induces Rapid-Onset Behavioral Sensitization and Cross-Sensitization with Cocaine in Mice: Implications for the Addictive Potential of Modafinil - Wuo-Silva, Raphael; Fukushiro, Daniela F.; Hollais, André W.; Santos-Baldaia, Renan; Mári-Kawamoto, Elisa; Berro, Laís F.; Yokoyama, Thaís S.; Lopes-Silva, Leonardo B.; Bizerra, Carolina S.; Procópio-Souza, Roberta; Hashiguchi, Debora; Figueiredo, Lilian A.; et al. (Frontiers in Pharmacology, 2016)
There is substantial controversy about the addictive potential of modafinil, a wake-promoting drug used to treat narcolepsy, proposed as pharmacotherapy for cocaine abuse, and used indiscriminately by healthy individuals due to its positive effects on arousal and cognition. The rapid-onset type of behavioral sensitization (i.e., a type of sensitization that develops within a few hours from the drug priming administration) has been emerged as a valuable tool to study binge-like patterns of drug abuse and the neuroplastic changes that occur quickly after drug administration that ultimately lead to drug abuse. Our aim was to investigate the possible development of rapid-onset behavioral sensitization to modafinil and bidirectional rapid-onset cross-sensitization with cocaine in male Swiss mice. A priming injection of a high dose of modafinil (64 mg/kg) induced rapid-onset behavioral sensitization to challenge injections of modafinil at the doses of 16 mg/kg, 32 mg/kg, and 64 mg/kg, administered 4h later. Furthermore, rapid-onset cross-sensitization was developed between modafinil and cocaine (64 mg/kg modafinil and 20 mg/kg cocaine), in a bidirectional way. These results were not due to residual levels of modafinil as the behavioral effects of the priming injection of modafinil were no longer present and modafinil plasma concentration was reduced at 4h post-administration. Taken together, the present findings provide preclinical evidence that modafinil can be reinforcing per se and can enhance the reinforcing effects of stimulants like cocaine within hours after administration.